Niat Melakukan Tes HIV Pada Eks Pekerja Migran Indonesia Di Kabupaten Lombok Timur - Satar Satar; Antono Suryoputro; Zahroh Shaluhiyah (Jurnal Promosi Kesehatan Indonesia, 2011)
HIV test is the only way to determine a person including former migrant workers contracting HIV / AIDS or not. Practice of HIV test is strongly influenced by intention to do it. This research is quantitative research with cross sectional nature explanations by using a questionnaire. Samples are former migrant workers in five districts in East Lombok taken by simple random sampling technique were 121 respondents. The results based on univariate test found 28.9% of respondents intend to conduct HIV tests. Factors associated with the intention of respondent to do an HIV test from the results of bivariate tests (chi-square test), namely the factors of knowledge about HIV / AIDS & HIV testing, attitudes toward HIV / AIDS & HIV testing and factors of self-efficacy perceptions of respondents to test for HIV. Multivariate analysis (logistic regression) found that there are two variables that influence intention to perform an HIV test that is self-efficacy variables (OR = 17.277 times) and the variable attitudes towards HIV / AIDS (OR = 7.4 times).